Zoledronic acid boosts γδ T-cell activity in children receiving αβ+ T and CD19+ cell-depleted grafts from an HLA-haplo-identical donor. (1st February 2017) - Bertaina, A.; Zorzoli, A.; Petretto, A.; Barbarito, G.; Inglese, E.; Merli, P.; Lavarello, C.; Brescia, L. P.; De Angelis, B.; Tripodi, G.; Moretta, L.; Locatelli, F.; et al.
ABSTRACT: We demonstrated that γδ T cells of patients given HLA-haploidentical HSCT after removal of αβ + T cells and CD19 + B cells are endowed with the capacity of killing leukemia cells after ex vivo treatment with zoledronic acid (ZOL). Thus, we tested the hypothesis that infusion of ZOL in patients receiving this type of graft may enhance γδ T-cell cytotoxic activity against leukemia cells. ZOL was infused every 28 d in 43 patients; most were treated at least twice. γδ T cells before and after ZOL treatments were studied in 33 of these 43 patients, till at least 7 mo after HSCT by high-resolution mass spectrometry, flow-cytometry, and degranulation assay. An induction of Vδ2-cell differentiation, paralleled by increased cytotoxicity of both Vδ1 and Vδ2 cells against primary leukemia blasts was associated with ZOL treatment. Cytotoxic activity was further increased in Vδ2 cells, but not in Vδ1 lymphocytes in those patients given more than one treatment. Proteomic analysis of γδ T cells purified from patients showed upregulation of proteins involved in activation processes and immune response, paralleled by downregulation of proteins involved in proliferation. Moreover, a proteomic signature was identified for each ZOL treatment. Patients given three or more ZOL infusions had a better probability of survival in comparison to those given one or two treatments (86% vs. 54%, respectively, p = 0.008). Our data indicate that ZOL infusion in pediatric recipients of αβ T- and B-cell-depleted HLA-haploidentical HSCT promotes γδ T-cell differentiation and cytotoxicity and may influence the outcome of patients.